2016
DOI: 10.1016/j.ajhg.2016.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous Loss-of-Function SEC61A1 Mutations Cause Autosomal-Dominant Tubulo-Interstitial and Glomerulocystic Kidney Disease with Anemia

Abstract: Autosomal-dominant tubulo-interstitial kidney disease (ADTKD) encompasses a group of disorders characterized by renal tubular and interstitial abnormalities, leading to slow progressive loss of kidney function requiring dialysis and kidney transplantation. Mutations in UMOD, MUC1, and REN are responsible for many, but not all, cases of ADTKD. We report on two families with ADTKD and congenital anemia accompanied by either intrauterine growth retardation or neutropenia. Ultrasound and kidney biopsy revealed sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
133
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 132 publications
(136 citation statements)
references
References 50 publications
1
133
1
1
Order By: Relevance
“…35 Two families have been identified with this condition. In one family, intrauterine growth retardation, dysplastic kidneys and anemia were present.…”
Section: Other Causes Of Adtkdmentioning
confidence: 99%
“…35 Two families have been identified with this condition. In one family, intrauterine growth retardation, dysplastic kidneys and anemia were present.…”
Section: Other Causes Of Adtkdmentioning
confidence: 99%
“…The CRISPR/ Cas9 efficiency was assessed as previously described. 49 In brief, DNA from each 2 day post fertilization (dpf) F0 embryo was extracted by proteinase K digestion (Life technologies, AM2548). The CRISPR-targeted region was amplified by PCR.…”
Section: Congenital Malformationsmentioning
confidence: 99%
“…Standard whole-mount zebrafish immunostaining was performed on CRISPR experiments as previously described. 49,50 To visualize the axonal tracts in the brain, including the optic tecta and the cerebellum, we stained 3 dpf mutant and control embryos with an anti-acetylated tubulin primary antibody (T7451, mouse, Sigma-Aldrich; 1:1,000 dilution) and the Alexa Fluor goat anti-mouse IgG (A21207, Invitrogen; 1:500 dilution) as a secondary antibody. 50 We observed that the size of the optic tecta was significantly smaller in CRISPR F0 mutants than in the control larvae (p % 0.0001, n ¼ 30-50 larvae/batch, repeated; Figures 4A and 4D).…”
Section: Congenital Malformationsmentioning
confidence: 99%
“…We and others have demonstrated previously the utility of zebrafish models in testing the candidacy of rare mutations in syndromic disorders; [14][15][16][17][18][19][20][21] this approach includes an experimental paradigm in which expression of mutations in the context of spliced isoforms can be used for testing the specific effect of such alleles. 14,22-24 For TMEM260, we utilized this approach to ask (1) whether the transient suppression or introduction of deletions at the locus can reproduce key aspects of the human pathology, (2) whether the two known isoforms of the human locus might have different abilities to rescue relevant phenotypes, and (3) whether the long TMEM260 isoform harboring individual 2-II-4's mutation (c.1698_1701del) has the ability to rescue relevant phenotypes.…”
Section: Renal Defectsmentioning
confidence: 99%
“…In addition to the rescue experiments, we tested the specificity of the phenotype by generating deletions in the zebrafish locus with CRISPR/Cas9-mediated genome editing. We designed and validated three CRISPR guide RNAs (G2, G3, and G4; Table S4) targeting exons 2, 7, and 5 of D. rerio tmem260, respectively, according to previously described methods, 16 and we injected guide RNA and Cas9 into single-cell embryos (n ¼ 48-74 embryos per batch). We established the efficiency of each reagent by genomic DNA isolation, heteroduplex detection on 15% polyacrylamide gel electrophoresis (n ¼ 6 embryos tested per condition), 25 and subsequent cloning and sequencing of PCR amplicons to estimate mosaicism.…”
Section: Renal Defectsmentioning
confidence: 99%